The Principal's Role as a Supervisor in Improving Teacher Professionalism - Okky Fadila; Retoliah Retoliah; Darmawansyah Darmawansyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study looks at how the principal at Persis Integrated Islamic Elementary School in Palu City may improve teacher professionalism as a supervisor. Direct observation and in-depth interviews with the principal and a number of instructors were used to gather data using a descriptive qualitative technique. The findings show that the principal's supervisory job is fulfilled through four primary responsibilities: coordinator, consultant, group leader, and evaluator. These duties are carried out through three primary phases: planning, implementation, and assessment. In their capacity as coordinator, the principal works with the vice principal to create a curriculum supervision program at the start of the semester based on an examination of the needs of the teachers and the academic schedule of the school. As a consultant, the principal offers specific advice based on each teacher's requirements and issues in a focused way. In their capacity as group leaders, the principal facilitates a teacher forum where educators can reflect together and share their experiences. The principal evaluates educational resources in an impartial and helpful manner in their capacity as an evaluator. Harmonious communication, clear schedules, teacher forums, specialised direction, and teacher gratitude are all supporting variables for supervision. Limited facilities, some teachers' unfavourable opinions on supervision, and the principal's time constraints from hectic administrative duties are also impediments